Enhancing soil ecosystem multifunctionality via carbon input and enzymatic catalysis in cover crops under antibiotic contamination - Ju Wang; Huanhuan Zhang; Jintao Yu; Xuechen Zhang; Mingjun Li; Peizhi Yang; Ziyan Li (Applied Soil Ecology, 2026)

Soil microplastic pollution shifts relative dominance in competition between native and invasive plants - Mingyan Li; Huizhen Zou; Zhihang Sun; Qiang Wang; Yanni Chen; Lina Xu; Change Zhou; Xianhu Guo; Shaoxia Guo; Chixuan Xiang; Xiaolei Jiang; Tong Wang; et al. (Applied Soil Ecology, 2026)

Soil microbiome and ecological traits depending on fertilization and climate in organic input agricultural ecosystem - Weiwei Li; Bangyu Zheng; Shibiao Cai; Xuechen Zhang; Ziyan Li; Wei Zheng; Bingnian Zhai; Yakov Kuzyakov (Applied Soil Ecology, 2026)

Integrated Physiological, Transcriptomic, and Gut Microbial Responses of Chinese Mitten Crab (Eriocheir sinensis) to Acute Salinity Stress - Yiming Li; Yucong Ye; Zongli Yao; Yan Li; Pengcheng Gao; Zhen Sun; Yuxing Wei; Kai Zhou; Binhong Guo; Yunlong Zhao; Qifang Lai (Marine Biotechnology, 2026)

Carrier–microbe coupling in an immobilized composite microbial agent enables enhanced PAE removal alongside carrier-mediated Cd stabilization in Cd–PAEs co-contaminated soil - Zhongning Liu; Junwei Tang; Qian Zhang; Junyu Xiang; Congyao Shi; Yan Liao; Siting Lu; Juanjuan Yin; Binhong Qin; Weiwei Yang; Chaolan Zhang (Journal of Soils and Sediments, 2026)

Predictive, preventive, and personalized medicine in statin-treated patients with NSTE-ACS, HFpEF, and type 2 diabetes: a data-driven model for long-term residual risk assessment - Zeyan Li; Hengyang Liu; Li Xu; Wenyuan Yin; Jiajun Zhu; Bowen Zhou; Bing Wu; Tongjian Zhu; Hui Li; Jinjun Liu; Yijun Wang; Jun Wang (EPMA Journal, 2026)

Untargeted UHPLC-MS/MS metabolomic profiling reveals organ-specific accumulation of metabolites in Gerbera piloselloides (L.) Cass - Yan Li; Juan Xue; Yongjia Shu; Ge Liu; Huifang Chai (Natural Product Research, 2026)

Context-dependent coupling between rhizosphere biochemical activation and SOC enrichment in croplands: a global meta-analysis - Ya-Jun Cheng; Jie-Yu-Xin Kang; Chun-Yan Li; Bai-Jian Lin; Yun Zhang; Jian-Ying Qi (Plant and Soil, 2026)

Biofabrication and artificial intelligence strategies for investigating solid- and fluid-pressure mechanobiology in pancreatic ductal adenocarcinoma - Yahui Ding; Peiyuan Zhao; Yan Jin; Yan Li; Zifei Wang; Ye Lu; Yichen Zhang; Hongzhuan Chen; Weidong Zhang; Xin Luan; Min Tang (Cancer and Metastasis Reviews, 2026)

Effects of Poly-γ-Glutamic Acid Application on Greenhouse Gas Emissions and GrainYield Under Different Direct-Seeding Methods in Paddy Rice - Rong Huang; Shi-hao Li; Hong-yan Li; Qian Luo; Yu-quan Fu; Qu-chen Zhou; Xiang-yu Huang; Xue-zhu Du; Feng Sheng (Journal of Soil Science and Plant Nutrition, 2026)

Experimental Study on the Mechanical Response and Damage Evolution Mechanism of Coal at Multiple Burial Depths Under True Triaxial Compensation Effect - Xin Xu; Guangming Zhao; Chongyan Liu; Minjie Qi; Qihang Zhang; Xukun Wu; Shuo Yang; Yian Chen (Rock Mechanics and Rock Engineering, 2026)

Unveiling Key Factors in Determining Biodegradable Mulching Film Adoption Through Evolutionary Game Analysis - Wanying Lin; Xi Mo; Luca Nizzetto; Xuan Shi; Yuan Chen; Jinhui Li; Yan Lin (Bulletin of Environmental Contamination and Toxicology, 2026)

Sedimentary DOM composition governs the environmental mobility of palladium in tropical island estuaries - Zhixin Li; Yuyan Liu; Ling Wang; Hongwei Yi; Rui Xu; Jianan Liu; Haofeng Liu; Ye Li; Min Liu (Marine Pollution Bulletin, 2026)

Soil fungal assembly in the wetlands in an arid environment of the Tarim Basin, China - Qiyan Li; Peishan Zhao; Guanglei Gao; Guodong Ding; Ying Zhang; Yilin Liu (Applied Soil Ecology, 2026)

Redistributing organic fertilizer from maize to wheat season improves soil functionality, microbial ecological networks, and annual crop yields in wheat–maize rotations - Xiaoying Chen; Zishuang Li; Huanyu Zhao; Yan Li; Jianlin Wei; Lei Ma; Fuli Zheng; Deshui Tan (Applied Soil Ecology, 2026)

Soil legacy effects in soybean intercropping enhance tobacco resistance to Fusarium root rot - Yuhao Dai; Chengzhi Wen; Zhijun Cheng; Zipeng Gao; Zhihui Wang; Peng Zhao; Mingshi Ding; Zhen Yang; Qiming Zhou; Jinpeng Gu; Dingguo Han; Lei Yang; et al. (Applied Soil Ecology, 2026)

Opportunistic bacteria enhancing inorganic phosphorus level in post-wildfire tropical forest peatlands - Pengfei Gao; Xiaoyu Cheng; Wen Tian; Hongmei Wang; Xiaoyan Liu; Olli H. Tuovinen; Thomas E.L. Smith; Stephanie L. Evers (Applied Soil Ecology, 2026)

Soil bacterial community assembly and driving factors in wetlands along the southern margin of the Tarim Basin - Linlin Zhang; Peishan Zhao; Guanglei Gao; Guodong Ding; Ying Zhang; Qiyan Li; Yilin Liu (Applied Soil Ecology, 2026)

Insights into the synergistic mechanism of petroleum-degrading bacterial consortium and Mirabilis jalapa L. combined remediation of crude oil-contaminated saline-alkali soil - Xinying Zhang; Yuchen Wan; Zongze Chen; Beibei Li; Xiaoyan Liu; Wenjing Yang; Ying Hao; Chuanhua Wang; Ling Yuan; Yongqi Wang (Applied Soil Ecology, 2026)

The impact of conversion of forest into cropland on soil nematode-associated microbiota varies across feeding habit of the host - Sisi Zhang; Cao Hao; Peng Zhang; Jingjing Yang; Meiyan Li; Pingting Guan; Donghui Wu (Applied Soil Ecology, 2026)

Niche-based filtering governs arbuscular mycorrhizal fungal community variation in temperate grasslands of Northern China - Xinyan Liu; Pengfei Wang; Hanting Qu; Zhiying Ding; Jingpeng Li; Da Xu; Fucheng Ding; Yuying Bao (Applied Soil Ecology, 2026)

Effects of silver nanoparticles and nitrile fungicides on soil microbial community structure, metabolic functions, and resistance genes - Yiwang Wang; Ting Gao; Jiajia Liu; Shaoheng Bao; Fuli Wang; Ge Yao; Xiaoyan Lin; Shijie Jiang; Jinlong Lai; Penggang Han; Jiang Hui (Applied Soil Ecology, 2026)

Drought-nitrogen synergy reshapes stress-adapted fungal consortia via plant-soil feedback in invasive plant Cenchrus pauciflorus - Meng Meng; Xiangning Yang; Bingna Wang; Haoyan Li; Chuan Lu; Jiahuan Li; Jiyun Yang; Long Bai; Yulong Feng; Baihui Ren (Applied Soil Ecology, 2026)

Soil multifunctionality driven by shift of bacterial rather than fungal community promotes cropland productivity via enhancing nitrogen use efficiency - Yanqiang Cao; Zengming Chen; Ye Li; Shiqi Xu; Cong Yang; Zhiyang Wu; Binbin Liu; Cunzhi Zhang; Deyan Liu; Bin Yin; Weixin Ding (Applied Soil Ecology, 2026)

Polyamide microplastic pollution modifies the sediment fungal structures associated with different submerged plant species: An insight from aquatic mesocosm experiment - Tong Wang; Jingwen Zhang; Xue Yang; Yinuo Zhu; Lin Qi; Mingyan Li; Xiao Guo; Hongwei Yu; Haifang Li (Applied Soil Ecology, 2026)

Plant diversity rather than soil microbial diversity drives the recovery of ecosystem multifunctionality during land restoration after rubber clearance - Qiang Lu; Xiaoqiang Lu; Xinli Chen; Xia Mao; Beibei Zhang; Jiaqi Li; Yan Liu; Xiangxiang Fu (Applied Soil Ecology, 2025)

Partial wool organic fertilizer substitution mitigate ammonia and nitrous oxide emissions and facilitate savoy cabbage growth - Jiahui Wang; Cun Sun; Shuyan Li; Yixun Shi; Hui Li; Jingchen Song; Jing Yuan; Wenhai Luo; Guoxue Li; Wen Liu; Guoxiang Bu; Hongbin Wang; et al. (Applied Soil Ecology, 2025)

Impacts of wheat straw and sulfate application on soil cadmium availability and bacterial community composition in two waterlogged soils with contrasting cadmium levels - Xianlin Ke; Yifei Li; Mingming Tao; Yanhua Qiu; Songyan Li; Xiaosong Yang; Zhengyi Hu (Applied Soil Ecology, 2025)

Nitrogen-salt interaction in Pennisetum giganteum: Effects on soil, rhizosphere, and ion transport processes - Peng Wang; Chen Zhang; Kok Sin Woon; Wenyu Li; Xu Pei; Mengxue Liu; Kun Zhang; Wenyan Li; Junkang Guo; Zhen Zhang; Yongtao Li (Applied Soil Ecology, 2025)

Insights into soil carbon metabolism and carbon sequestration capacity under organic fertilizer substitution model - Zirui Zhou; Yan Liao; Qian Zhang; Zicong Xiong; Junwei Tang; Jing Tian; Xiaolong Chang; Huailin Zhang; Junyu Xiang; Ziyuan Lin; Chaolan Zhang (Applied Soil Ecology, 2025)

Species interactions mediate arbuscular mycorrhizal fungi successional dynamics and glomalin-related soil protein accumulation in volcanic ecosystems - Pengfei Wang; Xinyan Liu; Yaxin Zheng; Hanting Qu; Jingpeng Li; Ruiping Wang; Yu Ji; Da Xu; Fucheng Ding; Peng Zhang; Haijing Liu; Yuying Bao (Applied Soil Ecology, 2025)

Inorganic amendment can delay the degradation of organic amendment by enhancing its resistance and mitigating microbial activities in saline–alkali soils - Shan Li; Yuanyuan Yao; Congling Zhou; Songyuan Wang; Zihan Liu; Yan Liu; Junyin Li; Guiwei Wang; Bin Gao; Dongdong Cheng; Yuechao Yang (Applied Soil Ecology, 2025)

Metagenomic insights into the effects of desiccation on functions associated with biogeochemical cycles and resistome of microbial communities - Lin Chen; Qiaoling Zhang; Wei Zhang; Kangyun Zhu; Qingyu Xu; Kaiming Hu; Qiuyue Feng; Yuyan Liu; Binhao Wang (Applied Soil Ecology, 2025)

Bacterial–fungal interkingdom interactions mediate effects of biodiversity on soil carbon dynamics in wheat fields under long-term fertilization - Wenguang Li; Jiarui Zhao; Tianyu Feng; Xuechen Zhang; Ziyan Li; Wei Zheng; Bingnian Zhai (Applied Soil Ecology, 2025)

Drought reinforces the relation between microbial activities and soil respiration but depresses the linkage between microbial activities and soil C and N: Evidence from rhizosphere in rapeseed (Brassica napu) - Qiwen Xu; Bo Zhu; Meichun Duan; Bangyan Liu; Longchang Wang (Applied Soil Ecology, 2025)

Sheep dung addition and reseeding promote ecosystem multifunctionality by mediating soil microbial network complexity in a subtropical grassland - Debao Li; Haibian Xu; Yan Li; Jinghang Xu; Meiyan Zhang; Jianping Wu (Applied Soil Ecology, 2025)

Magnetic characteristics and source analysis of modern snow dust from the Tianshan Mountains - Yan Liu; Jia Jia; Lai Zhao; Yixiao Zhang; Junhuai Yang; Zhenhao Zhu; Yijiao Fan; Ziwei Tao; Zhenyuan Yao (Aeolian Research, 2025)

Opposing island biogeographic effects of turnover and nestedness on beta-diversity of soil faunal communities between woodland and deforested grassland - Zengyan Li; Zengke Zhang; Anna Yang; Sufeng Pan; Junyong Zheng; Ling Mou; Wensheng Chen; Tian Zhang; Liyi Zhou; Wenhui You; David A. Wardle; En-Rong Yan (Applied Soil Ecology, 2025)

Increased carbon sequestration of different straw return depths varies temporally - Jin Li; Xiaoyu Li; Ling Ma; Guangyan Liu; Yanyu Han; Jiaqi Li; Roland Bol; Hongtao Zou (Applied Soil Ecology, 2025)

12-year N addition enhances soil organic carbon decomposition by mediating microbial community composition in temperate plantations - Xinyi Wu; Yanyan Liu; Hongjin Zhang; Lizheng Dong; Yiping Zuo; Xiaoyue Li; Wei Wang (Applied Soil Ecology, 2025)

Origin and assembly characteristics of periphyton microbes in subtropical paddy fields: A case study in Tuojia catchment in Southern China - Zongming Li; Jie He; Jianlin Shen; Yanyan Li; Quan Yuan; Qihong Zhu; Jinshui Wu (Applied Soil Ecology, 2025)

A simplified multi-model statistical approach for predicting the effects of forest management on land surface temperature in Fennoscandia - Bo Huang; Yan Li; Yi Liu; Xiangping Hu; Wenwu Zhao; Francesco Cherubini (Agricultural and Forest Meteorology, 2023)

Characterizing spatial, diurnal, and seasonal patterns of agricultural irrigation expansion-induced cooling in Northwest China from 2000 to 2020 - Chao Zhang; Quansheng Ge; Jinwei Dong; Xuezhen Zhang; Yan Li; Songjun Han (Agricultural and Forest Meteorology, 2023)

A 12‐point checklist for surveillance of diseases of aquatic organisms: a novel approach to assist multidisciplinary teams in developing countries - Melba G. Bondad‐Reantaso; Nihad Fejzic; Brett MacKinnon; David Huchzermeyer; Sabina Seric‐Haracic; Fernando O. Mardones; Chadag Vishnumurthy Mohan; Nick Taylor; Mona Dverdal Jansen; Saraya Tavornpanich; Bin Hao; Jie Huang; et al. (Reviews in Aquaculture, 2021)
A 12‐point checklist in the design and practical application of active surveillance of diseases in aquatic organisms (farmed and wild) has been developed to serve as a methodological approach and guidance for a multidisciplinary team particularly in countries where surveillance expertise is limited. The checklist is based on a review of available main aquatic surveillance references and scientific literature and was further developed based on the outcomes of several aquaculture biosecurity project‐related workshops hosted by the Food and Agriculture Organization of the United Nations. The checklist includes the following: (1) scenario setting; (2) defining surveillance objective; (3) defining the populations; (4) disease clustering; (5) case definition; (6) diagnostic testing; (7) study design and sampling; (8) data collection and management; (9) data analysis; (10) validation and quality assurance; (11) human and financial resources and logistics requirements; and (12) surveillance in the bigger picture. For a multidisciplinary approach to disease control, knowledge of fish biology, aquaculture systems and many aspects of aquaculture health management are required. Surveillance needs significant financial investment and must be supported by adequate diagnostic capability, information system management, legal framework and communication networks, with transparent reporting mechanisms to allow rapid disease response for serious diseases of aquatic organisms. It is a stepwise and pragmatic approach that offers a good starting point for addressing disease issues especially in developing countries. It can be used as a model to build targeted surveillance competency and a basic reference when implementing a surveillance programme or improving existing programmes.

Role of winds and tides in timing of beach strandings, occurrence, and significance of swarms of the jellyfish Crambione mastigophora Mass 1903 (Scyphozoa: Rhizostomeae: Catostylidae) in north-western Australia - John K. Keesing; Lisa-Ann Gershwin; Tim Trew; Joanna Strzelecki; Douglas Bearham; Dongyan Liu; Yueqi Wang; Wolfgang Zeidler; Kimberley Onton; Dirk Slawinski (Hydrobiologia, 2016)

Effects of intensive scallop mariculture on macrobenthic assemblages in Sishili Bay, the northern Yellow Sea of China - Qingxi Han; Yueqi Wang; Yong Zhang; John Keesing; Dongyan Liu (Hydrobiologia, 2013)